ANALISIS TENTANG FAKTOR-FAKTOR YANG MEMENGARUHI INITIAL RETURN PADA IPO DI BURSA EFEK INDONESIA - Hendratni, Tyahya Whisnu (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The initial return on initial public offering (IPO) in Indonesian Stock Exchange (ISX) was stated to be under-pricing. However, the underpricing of initial return was still inconclusive. Some of the previous findings showed that the initial return on IPO tended to be under-priced and the expectation of the initial return to being over-pricing still could not be achieved. This study state that the initial listing price has not been related to initial return to achieve the expecting price in the long run. The influence of age of listed companies and the excess of paid in capital on an initial return of the IPO were significant, this is because the underwriter’s pressure on listed companies to put their listing price below the expecting price. Keywords: initial public offering, stock market